Mutual Partnership Model between Plant Breeder and Gapoktan-Ponpes (A Traditional Farmer Group) in Pre-releasing New Hybrid and Composite Varieties of Sweet Corn - Arifin Noor Sugiharto; Agus Suryanto (Research Journal of Life Science, 2014)
We have been genotyping the Filius (F6) sweet corn lines that currently ready to be evaluated by multi-location and heterosis test.Normally, in the step of breeding program, releasing varieties followed by seed production and distribution would be done after such tests that  costly needed and time consuming. Traditional institution of farmer group called in Indonesia as “Gapoktan” and the Religious teaching stage called as “Ponpes” have been  known as non-formal institution which have high potency and unique networking access to surrounding public citizen and other informal institutions.  As so did, they can be as a producer and virtual guarantor or good marketing agent of many agricultural products as well. Therefore, a mutual partnership model established between breeder and them is very important and to be a prospective idea to short cut breeding process and hybrid seed production. Scientific accountability and efficiency of whole breeding – seed production would be kept into main consideration. The concept was “Gapoktan” and “Ponpes” firstly would be trained to adopt technology for crossing to set F1 Hybrid seed, then the results would be evaluated and compared with those done by breeder to determine whether they eligible or not. If they did so, partnership would be mutully continued and they would be encouraged to distribute F1 seeds to other “gapoktan” or public citizens. Three nominated Gapoktan and Ponpes from separated regencies, i.e., Pasuruan, Malang and Batu were determined as the model.The results showed that F1 seed production variable as indicator achievement of them were not significantly different from those of breeder in any place. Even though in between the places they did differ in several vegetative and productive factors each other. The differences were probably caused by ecological factors, not by their capability in agriculture practicing. Based on standard of common farming of corn or sweet corn in East Java, benefit gain increment by farmer caused by such partnership in F1seed production reached about 150% to 247%. So that, partnership model for producing multi-location test as well as producing hybrid seeds between Breeder-Gapoktan-Ponpes was economically prospective and scientifically eligible to do so. On the benefit consideration gained by farmers, Pasuruan was the place where the most attractive to be done partnership model followed by Malang and Batu.